89.8k views
1 vote
Find the 5th term of the expansion of ( 6x + 6y)^11

1 Answer

7 votes

The 5 th term of the given expression is 330
(6x)^(7)( 6y)^(4).

Explanation:

Given,


(6x+6y)^(11)

To find the 5th term of the given expression.

Formula

In a binomial series
(a+b)^(n), the r th term is = nC(r-1)
a^(n-r-1) b^(r-1), where,

nC(r-1) =
(n!)/((r-1)!(n-r+1)!)

Now,

Putting, n=11, r = r, a=6x and b=6y we get,

5 th term = 11C4
(6x)^(7)( 6y)^(4)

=
(11!)/(4!7!)
(6x)^(7)( 6y)^(4)

=
(11X10X9X8X7!)/(7!X4X3X2X1)
(6x)^(7)( 6y)^(4)

= 330
(6x)^(7)( 6y)^(4)

Here is the answer.

User Kaushalpranav
by
6.0k points